2017
DOI: 10.1016/j.ijid.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Emerging group C and group G streptococcal endocarditis: A Canadian perspective

Abstract: IE from GCGS bacteremia is common and is frequently associated with severe disease, embolic events, and mortality. In the appropriate clinical context, GCGS bacteremic events should prompt investigation for IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Previous studies have demonstrated SD-caused IE as having an acute onset of illness and high mortality similar to S. aureus-caused IE [9,11]. Furthermore, Lother et al showed that 6% of patients with GCS or GGS bacteremia developed IE with extensive need of intensive care unit treatment but of these cases only two were verified at the species level as SD [10]. As with other types of invasive SD infections [29], old males are the typical patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have demonstrated SD-caused IE as having an acute onset of illness and high mortality similar to S. aureus-caused IE [9,11]. Furthermore, Lother et al showed that 6% of patients with GCS or GGS bacteremia developed IE with extensive need of intensive care unit treatment but of these cases only two were verified at the species level as SD [10]. As with other types of invasive SD infections [29], old males are the typical patients.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Lother et al identified 12 cases with group C-or G-caused IE, four cases of definitive, and eight cases of possible IE, out of 209 events of groups C and G bacteremia. Of these 12 cases, a majority had embolic events with rapid and progressive disease and considerable mortality rate [10]. Other studies have focused on all β-hemolytic streptococci (BHS) and typically the majority of cases have been attributed to group B streptococci, with no species determination performed to determine if some isolates were SD.…”
Section: Introductionmentioning
confidence: 99%
“…Notable exceptions included Streptococcus intermedius, Streptococcus pyogenes (Lancefield group A), Streptococcus agalactiae (Lancefield group B), and Streptococcus dysgalactiae (Lancefield group G), with MIC ranges of 0.06 to 0.5, 0.5 to 4, 0.25 to 4, and 1 to 2 g/ml, respectively. Unlike many of the viridans streptococci and E. faecalis which primarily cause subacute IE, S. intermedius (a viridans group species) and both S. agalactiae and S. dysgalactiae are, interestingly, associated with the more aggressive acute disease caused by staphylococci and resulting in rapid destruction of the endocardium (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…According to current guidelines, SDSE is considered to be a rare causative pathogen of IE; however, a recent report concluded that IE occurred in 6% of patients with group C and G streptococci bacteremia, 4 showing that the risk of endocarditis is not negligible when SDSE is positive in blood cultures. Endocarditis involving the native valve 5,6 and prosthetic valve 7 has been reported, as well as cardiac device‐related endocarditis 8 .…”
Section: Discussionmentioning
confidence: 99%